Condom bubble lubricant containing hyaluronic acid and preparation method thereof

Through the combination of microfluidic droplet technology and specific ratios, a condom bubble lubricant containing hyaluronic acid is prepared, which solves the problems of lubricant stability and safety, achieves efficient lubrication, moisturizing, sterilization and soothing effects, and is suitable for condom lubricants.

CN120605381APending Publication Date: 2025-09-09BEIJING DAXIANG & HIS FRIENDS TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510955986.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-11
Publication Date
2025-09-09

AI Technical Summary

Technical Problem

In the prior art, hyaluronic acid lubricants have poor lubrication effects in condoms, poor stability, are prone to rupture, increase viscosity, and are prone to allergies, and cannot meet the requirements of high lubricity and safety.

Method used

Microfluidic droplet technology is used to prepare condom bubble lubricant containing hyaluronic acid. By controlling the ratio and flow rate of the water phase and the oil phase, an oil-in-water emulsion is formed, and citric acid is added for stability. Sodium alginate and calcium ethylenediaminetetraacetic acid are combined to form gel-like small droplets. Green tea extract and glutathione are used to enhance the lubrication and moisturizing effects. Dialdehyde cellulose and green tea extract are used synergistically to improve affinity and antibacterial and antipruritic effects.

Benefits of technology

It has good lubrication effect, moisturizing and soothing, cleaning and lubricating, sterilization and itching relief, avoids allergies, has a long lubrication time, and is non-sticky, making it suitable for large-scale promotion and application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120605381A_ABST
    Figure CN120605381A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of human body lubricants, and particularly discloses a condom bubble lubricant containing hyaluronic acid and a preparation method of the condom bubble lubricant. The condom bubble lubricant containing hyaluronic acid is prepared from the following raw materials in parts by mass: 5 to 10 parts of hyaluronic acid, 1 to 3 parts of sodium alginate, 0.01 to 0.1 part of calcium ethylene diamine tetraacetate, 1 to 2 parts of nano silicon dioxide, 1 to 2 parts of surfactant, 60 to 120 parts of vegetable oil, 1 to 2 parts of citric acid, 1 to 2 parts of green tea extract, 1 to 2 parts of glutathione, 5 to 10 parts of plant essential oil, 1 to 3 parts of dialdehyde cellulose and 50 to 90 parts of water. According to the invention, the vagina can be effectively protected, the vagina mucosa can be effectively repaired, the immunoreaction can be effectively reduced, the good inhibition effect on common pathogenic bacteria is realized, the biocompatibility of the components and the human skin is high, the micro-ecological environment of the cavity is improved, the allergy and stimulation effects are avoided, the raw materials are easy to obtain, the operation is easy, and the reaction conditions are mild.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of human body lubricants, and in particular to a condom bubble lubricant containing hyaluronic acid and a preparation method thereof. Background Art

[0002] Personal lubricants are specially designed for the human body, offering wide applicability and high safety. With technological advancements and rising living standards, people's expectations for condom use are becoming increasingly stringent, primarily in terms of lubricity. Early use of vegetable oils was not only ineffective, easily staining clothing, but also difficult to absorb. Mineral oils like petroleum jelly and massage oils are also highly viscous, difficult to clean, and prone to leaving residue.

[0003] Hyaluronic acid, also known as hyaluronic acid, has a molecular formula of (C 14 H 21 NO 11 ) n Hyaluronic acid is a glycosaminoglycan composed of disaccharide units of D-glucuronic acid and N-acetylglucosamine. As an acidic mucopolysaccharide, its unique molecular structure and physicochemical properties demonstrate a variety of important physiological functions in the body, such as lubricating joints, regulating the permeability of blood vessels, regulating the diffusion and movement of proteins, water, and electrolytes, and promoting wound healing.

[0004] Microfluidic droplet technology is a microfabrication technique that uses microfluidic chips to precisely control immiscible multiphase fluids. Compared to traditional water-in-oil (W / O) or oil-in-water (O / W) single emulsion droplet technology, the resulting micro-bead multiphase emulsion, with its unique oil-water separation structure, can dissolve substances with different properties in different phases, presenting a unique appearance and providing isolation, protection, and sustained-release functions. It not only has a better moisturizing effect than traditional oil-in-water (O / W) emulsions, but also has a better texture and less stickiness than water-in-oil (W / O) emulsions. It overcomes the shortcomings of traditional two-phase emulsions while retaining their advantages.

[0005] Using hyaluronic acid in microfluidic droplet technology to create a condom bubble lubricant has great potential for application. However, existing technologies utilize the interaction of aqueous and oil phases within a microfluidic chip. The resulting hydrogels are unstable and prone to rupture after polymerization or cross-linking. This results in poor lubrication and a short lubrication duration, increased viscosity, and a high risk of allergic reactions, limiting their use. Summary of the Invention

[0006] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a condom bubble lubricant containing hyaluronic acid and a preparation method thereof.

[0007] A hyaluronic acid-containing condom bubble lubricant comprises the following raw materials in parts by mass: 5-10 parts of hyaluronic acid, 1-3 parts of sodium alginate, 0.01-0.1 parts of calcium edetate, 1-2 parts of nano-silicon dioxide, 1-2 parts of surfactant, 60-120 parts of vegetable oil, 1-2 parts of citric acid, 1-2 parts of green tea extract, 1-2 parts of glutathione, 5-10 parts of plant essential oil, 1-3 parts of dialdehyde cellulose, and 50-90 parts of water.

[0008] Preferably, the surfactant is at least one of lauryl alcohol polyoxyethylene ether, stearyl alcohol polyoxyethylene ether, cetyl polyoxyethylene ether, cetearyl alcohol polyoxyethylene ether, sorbitan fatty acid ester, and polyoxyethylene sorbitan fatty acid ester.

[0009] Preferably, the vegetable oil is at least one of peanut oil, rapeseed oil, corn oil, camellia oil, walnut oil, olive oil, palm oil, grapeseed oil, and sunflower oil.

[0010] Preferably, the green tea extract is prepared by the following steps: crushing freshly picked green tea leaves, first using a 50-60% by mass ethanol aqueous solution for reflux extraction for 2-4 hours, then using a 70-80% by mass ethanol aqueous solution for reflux extraction for 1-2 hours, combining the extracts, distilling under reduced pressure to recover ethanol, concentrating, then adding chloroform and stirring for 1-2 hours, letting it stand to separate the layers, and taking the upper layer solution and freeze-drying it.

[0011] Preferably, the mass ratio of freshly picked green tea leaves to 50-60% ethanol aqueous solution, 70-80% ethanol aqueous solution, and chloroform is 5-10:30-50:20-40:30-50.

[0012] Preferably, the plant essential oil is rose essential oil, ylang-ylang essential oil, sandalwood essential oil or / and maca essential oil.

[0013] Among them, dialdehyde cellulose can be found in the literature [1].

[0014] [1] Shi Lei, Zhen Wenjuan, Shan Zhihua. Preparation and characterization of dialdehyde cellulose[J]. Fine Chemicals, 2008, 25(8):4. DOI:10.3321 / j.issn:1003-5214.2008.08.016.

[0015] The method for preparing the above-mentioned condom bubble lubricant containing hyaluronic acid comprises the following steps:

[0016] S1. Add sodium alginate, calcium EDTA, and hyaluronic acid to water, stir and dissolve at 55-65°C, add nano-silica and continue stirring for 1-2 hours to obtain an aqueous phase;

[0017] S2. Adding a surfactant to the vegetable oil and stirring evenly to obtain an oil phase;

[0018] S3. Prepare a water-in-oil emulsion from the aqueous phase and the oil phase by microfluidic droplet technology, then add citric acid thereto under stirring, ultrasonically treat for 1-2 minutes, let stand to remove the oil phase, add green tea extract, glutathione, plant essential oil, dialdehyde cellulose, and water to the product, stir at 40-50°C for 10-30 minutes, and adjust the pH value of the system to 5.5-6.5.

[0019] Preferably, in S3, in the process of preparing the water-in-oil emulsion using microfluidic droplet technology, the water phase flow rate is 200-300 μL / h, and the oil phase flow rate is 600-800 μL / h.

[0020] Preferably, in S3, the ultrasonic frequency is 5-12 kHz.

[0021] Preferably, the mass ratio of water used in S1 to water used in S3 is 20-30:30-60.

[0022] Beneficial effects:

[0023] The present invention adopts hyaluronic acid in combination with sodium alginate and calcium EDTA, which are dissolved in water to form an aqueous phase. By controlling the ratio and flow rate of the aqueous phase and the oil phase, a water-in-oil emulsion is formed by shearing. The density of the aqueous phase droplets is relatively low, so they float on the upper layer of the oil phase. Citric acid is added to the emulsion system and diffused into the aqueous phase, resulting in reduced stability of the calcium EDTA, which then becomes free and combines with the sodium alginate to form gel-like droplets. The oil phase is further removed to obtain hydrophilic droplet particles, which not only have a good lubricating effect, but also have excellent moisturizing and soothing effects. They further act synergistically with green tea extract and glutathione, have good affinity, and are highly dispersed uniformly with each other. They can not only significantly improve vaginal dryness, but also have excellent cleaning and lubricating effects, and have good antibacterial and antipruritic effects.

[0024] This invention combines dialdehyde cellulose with the phenolic hydroxyl groups on green tea extract, effectively extending its bactericidal and antibacterial properties. It also works with glutathione to neutralize oxidation, protecting vaginal cells from oxidative damage. This invention effectively prevents allergies and other problems, eliminates any sticky sensation after use, and provides long-lasting lubrication, providing a comfortable and natural feel.

[0025] The present invention can effectively protect the vagina and repair the vaginal mucosa, effectively reduce the immune response, and has a good inhibitory effect on common pathogens. At the same time, the ingredients have high biocompatibility with human skin, improve the cavity microecological environment, and do not have allergic or irritating effects. Moreover, the raw materials are easily available, easy to operate, the reaction conditions are mild, the effect is obvious, and it is suitable for large-scale promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1The graph is a comparison of the viscosity and lubricity of the lubricants obtained in Example 5 and Comparative Examples 1-2.

[0027] Figure 2 The figure is a comparison chart of the moisturizing performance and burst pressure retention rate of the lubricants obtained in Example 5 and Comparative Examples 1-2.

[0028] Figure 3 This is a comparison chart of the antibacterial rates of the lubricants obtained in Example 5 and Comparative Examples 1-2 against Escherichia coli 8099, Staphylococcus aureus ATCC6538, and Candida albicans ATCC10231. DETAILED DESCRIPTION

[0029] The present invention will be further explained below with reference to specific embodiments.

[0030] Example 1

[0031] A hyaluronic acid-containing condom bubble lubricant, whose raw materials include: 5g hyaluronic acid, 1g sodium alginate, 0.01g calcium edetate, 1g nano-silicon dioxide, 601g Span, 60g olive oil, 1g citric acid, 1g green tea extract, 1g glutathione, 5g ylang-ylang essential oil, 1g dialdehyde cellulose, and 50g water.

[0032] Green tea extract is prepared by the following steps: 5g of freshly picked green tea leaves are crushed, first extracted with 30g of 50% ethanol aqueous solution by mass for 2h, then extracted with 20g of 70% ethanol aqueous solution by mass for 1h, the extracts are combined, ethanol is recovered by vacuum distillation, and the water content is concentrated to 20%, followed by adding 30g of chloroform, stirring at 100r / min for 1h, allowing to stand and separate, and the upper layer solution is freeze-dried.

[0033] The method for preparing the above-mentioned condom bubble lubricant containing hyaluronic acid comprises the following steps:

[0034] S1. Sodium alginate, calcium EDTA, and hyaluronic acid were added to 20 g of water, stirred and dissolved at 55°C, and nano-silica was added thereto, and stirring was continued for 1 h at a stirring speed of 50 r / min to obtain an aqueous phase;

[0035] S2. Add Span 60 to the olive oil and stir evenly to obtain an oil phase;

[0036] S3. The aqueous phase and the oil phase are respectively injected into the microchannel of the microfluidic device by a syringe through a constant flow pump, the flow rate of the aqueous phase is 200 μL / h, and the flow rate of the oil phase is 600 μL / h, wherein the oil phase shears the aqueous phase into an oil-in-water emulsion; citric acid is added thereto under stirring, ultrasonic treatment is performed for 1 minute, the ultrasonic frequency is 5 kHz, and the oil phase is removed by standing. Green tea extract, glutathione, ylang-ylang essential oil, dialdehyde cellulose, and 30 g of water are added to the product, and the mixture is stirred at a temperature of 40°C for 10 minutes to adjust the pH value of the system to 5.5-6.5.

[0037] Example 2

[0038] A hyaluronic acid-containing condom bubble lubricant, whose raw materials include: 10g hyaluronic acid, 3g sodium alginate, 0.1g calcium EDTA, 2g nano-silicon dioxide, 2g Span 80, 120g sunflower seed oil, 2g citric acid, 2g green tea extract, 2g glutathione, 10g maca essential oil, 3g dialdehyde cellulose, and 90g water.

[0039] Green tea extract is prepared by the following steps: 10g of freshly picked green tea leaves are crushed, first extracted with 50g of 60% ethanol aqueous solution by mass for 4h, then extracted with 40g of 80% ethanol aqueous solution by mass for 2h, the extracts are combined, ethanol is recovered by vacuum distillation, and the water content is concentrated to 30%, followed by adding 50g of chloroform, stirring at 200r / min for 2h, allowing to stand and separate, and the upper layer solution is freeze-dried.

[0040] The method for preparing the above-mentioned condom bubble lubricant containing hyaluronic acid comprises the following steps:

[0041] S1. Sodium alginate, calcium EDTA, and hyaluronic acid were added to 30 g of water, stirred and dissolved at 65°C, and nano-silica was added thereto, and stirring was continued for 2 h at a stirring speed of 120 r / min to obtain an aqueous phase;

[0042] S2. Add Span 80 to the sunflower oil and stir evenly to obtain an oil phase;

[0043] S3. The aqueous phase and the oil phase are injected into the microchannel of the microfluidic device respectively by a syringe through a constant flow pump, the flow rate of the aqueous phase is 300 μL / h, and the flow rate of the oil phase is 800 μL / h, wherein the oil phase shears the aqueous phase into an oil-in-water emulsion; citric acid is added thereto under stirring, ultrasonic treatment is performed for 2 minutes, the ultrasonic frequency is 12 kHz, and the oil phase is removed by standing. Green tea extract, glutathione, maca essential oil, dialdehyde cellulose, and 60 g of water are added to the product, and stirred at a temperature of 50°C for 30 minutes. The pH value of the system is adjusted to 5.5-6.5.

[0044] Example 3

[0045] A hyaluronic acid-containing condom bubble lubricant, comprising raw materials including: 7g hyaluronic acid, 2.5g sodium alginate, 0.03g calcium edetate, 1.7g nano-silica, 1.2g Tween 60, 100g olive oil, 1.3g citric acid, 1.8g green tea extract, 1.3g glutathione, 9g rose essential oil, 1.5g dialdehyde cellulose, and 62g water.

[0046] Green tea extract is prepared by the following steps: 9 g of freshly picked green tea leaves are crushed, first reflux extracted with 35 g of 58% ethanol aqueous solution by mass for 2.5 hours, then reflux extracted with 35 g of 73% ethanol aqueous solution by mass for 100 minutes, the extracts are combined, and the ethanol is recovered by vacuum distillation and concentrated to a water content of 22%. Then, 45 g of chloroform is added, stirred at a speed of 120 r / min for 100 minutes, allowed to stand to separate, and the upper layer solution is freeze-dried.

[0047] The method for preparing the above-mentioned condom bubble lubricant containing hyaluronic acid comprises the following steps:

[0048] S1. Sodium alginate, calcium EDTA, and hyaluronic acid were added to 22 g of water, stirred and dissolved at 62°C, and nano-silica was added thereto, and stirring was continued for 80 min at a stirring speed of 110 r / min to obtain an aqueous phase;

[0049] S2. Add Tween 60 to olive oil and stir evenly to obtain an oil phase;

[0050] S3. The aqueous phase and the oil phase are injected into the microchannel of the microfluidic device respectively by a syringe through a constant flow pump, the flow rate of the aqueous phase is 220 μL / h, and the flow rate of the oil phase is 750 μL / h, wherein the oil phase shears the aqueous phase into an oil-in-water emulsion; citric acid is added thereto under stirring, ultrasonic treatment is performed for 80 seconds, the ultrasonic frequency is 9 kHz, and the oil phase is removed by standing. Green tea extract, glutathione, rose essential oil, dialdehyde cellulose, and 40 g of water are added to the product, and the mixture is stirred at a temperature of 48°C for 15 minutes. The pH value of the system is adjusted to 5.5-6.5.

[0051] Example 4

[0052] A hyaluronic acid-containing condom bubble lubricant, comprising the following raw materials: 9g hyaluronic acid, 1.5g sodium alginate, 0.07g calcium EDTA, 1.3g nano-silicon dioxide, 1.8g Tween 80, 80g camellia oil, 1.7g citric acid, 1.2g green tea extract, 1.7g glutathione, 7g rose essential oil, 2.5g dialdehyde cellulose, and 78g water.

[0053] Green tea extract is prepared by the following steps: 7g of freshly picked green tea leaves are crushed, first extracted with 45g of 52% ethanol aqueous solution by mass for 3.5h, then extracted with 25g of 77% ethanol aqueous solution by mass for 80min, the extracts are combined, and the ethanol is recovered by vacuum distillation and concentrated to a water content of 28%. Then, 35g of chloroform is added, stirred at 180r / min for 80min, allowed to stand and separate, and the upper layer solution is freeze-dried.

[0054] The method for preparing the above-mentioned condom bubble lubricant containing hyaluronic acid comprises the following steps:

[0055] S1. Sodium alginate, calcium EDTA, and hyaluronic acid were added to 28 g of water, stirred and dissolved at 58°C, and nano-silica was added thereto, and the mixture was stirred for 100 min at a stirring speed of 90 r / min to obtain an aqueous phase.

[0056] S2. Add Tween 80 to the camellia oil and stir evenly to obtain an oil phase;

[0057] S3. The aqueous phase and the oil phase are respectively injected into the microchannel of the microfluidic device by a syringe through a constant flow pump, the flow rate of the aqueous phase is 280 μL / h, and the flow rate of the oil phase is 650 μL / h, wherein the oil phase shears the aqueous phase into an oil-in-water emulsion; citric acid is added thereto under stirring, ultrasonic treatment is performed for 100 s, the ultrasonic frequency is 6 kHz, and the oil phase is removed by standing. Green tea extract, glutathione, rose essential oil, dialdehyde cellulose, and 50 g of water are added to the product, and the mixture is stirred at a temperature of 42°C for 25 min. The pH value of the system is adjusted to 5.5-6.5.

[0058] Example 5

[0059] A hyaluronic acid-containing condom bubble lubricant, whose raw materials include: 8g hyaluronic acid, 2g sodium alginate, 0.05g calcium edetate, 1.5g nano-silicon dioxide, 1.5g Span 60, 90g palm oil, 1.5g citric acid, 1.5g green tea extract, 1.5g glutathione, 8g rose essential oil, 2g dialdehyde cellulose, and 70g water.

[0060] Green tea extract is prepared by the following steps: 8g of freshly picked green tea leaves are crushed, first extracted with 40g of 55% ethanol aqueous solution by mass for 3h, then extracted with 30g of 75% ethanol aqueous solution by mass for 90min, the extracts are combined, and the ethanol is recovered by vacuum distillation and concentrated to a water content of 25%. Then, 40g of chloroform is added, stirred at a speed of 150r / min for 90min, allowed to stand and separate, and the upper layer solution is freeze-dried.

[0061] The method for preparing the above-mentioned condom bubble lubricant containing hyaluronic acid comprises the following steps:

[0062] S1. Sodium alginate, calcium EDTA, and hyaluronic acid were added to 25 g of water, stirred and dissolved at 60° C. Nano-silica was added thereto and stirred for 90 min at a stirring speed of 100 rpm to obtain an aqueous phase.

[0063] S2. Add Span 60 to palm oil and stir evenly to obtain an oil phase;

[0064] S3. The aqueous phase and the oil phase are injected into the microchannel of the microfluidic device respectively by a syringe through a constant flow pump, the flow rate of the aqueous phase is 260 μL / h, and the flow rate of the oil phase is 700 μL / h, wherein the oil phase shears the aqueous phase into an oil-in-water emulsion; citric acid is added thereto under stirring, ultrasonic treatment is performed for 90 seconds, the ultrasonic frequency is 7.5 kHz, and the oil phase is removed by standing. Green tea extract, glutathione, rose essential oil, dialdehyde cellulose, and 45 g of water are added to the product, and the mixture is stirred at a temperature of 45°C for 20 minutes. The pH value of the system is adjusted to 5.5-6.5.

[0065] Comparative Example 1

[0066] A hyaluronic acid-containing condom bubble lubricant, whose raw materials include: 8g hyaluronic acid, 2g sodium alginate, 0.05g calcium EDTA, 1.5g nano-silicon dioxide, 1.5g Span 60, 90g palm oil, 1.5g green tea extract, 1.5g glutathione, 8g rose essential oil, 2g dialdehyde cellulose, and 70g water.

[0067] Green tea extract is prepared by the following steps: 8g of freshly picked green tea leaves are crushed, first extracted with 40g of 55% ethanol aqueous solution by mass for 3h, then extracted with 30g of 75% ethanol aqueous solution by mass for 90min, the extracts are combined, and the ethanol is recovered by vacuum distillation and concentrated to a water content of 25%. Then, 40g of chloroform is added, stirred at a speed of 150r / min for 90min, allowed to stand and separate, and the upper layer solution is freeze-dried.

[0068] The method for preparing the above-mentioned condom bubble lubricant containing hyaluronic acid comprises the following steps:

[0069] S1. Sodium alginate, calcium EDTA, and hyaluronic acid were added to 25 g of water, stirred and dissolved at 60° C. Nano-silica was added thereto and stirred for 90 min at a stirring speed of 100 rpm to obtain an aqueous phase.

[0070] S2. Add Span 60 to palm oil and stir evenly to obtain an oil phase;

[0071] S3. The aqueous phase and the oil phase are respectively injected into the microchannel of the microfluidic device by a syringe through a constant flow pump. The flow rate of the aqueous phase is 260 μL / h, and the flow rate of the oil phase is 700 μL / h. The oil phase shears the aqueous phase into an oil-in-water emulsion. Ultrasonic treatment is performed for 90 seconds at an ultrasonic frequency of 7.5 kHz to remove the oil phase. Green tea extract, glutathione, rose essential oil, dialdehyde cellulose, and 45 g of water are added to the product. The mixture is stirred at 45°C for 20 minutes and the pH value of the system is adjusted to 5.5-6.5.

[0072] Comparative Example 2

[0073] A hyaluronic acid-containing condom bubble lubricant, whose raw materials include: 8g hyaluronic acid, 2g sodium alginate, 0.05g calcium EDTA, 1.5g nano-silicon dioxide, 1.5g Span 60, 90g palm oil, 1.5g citric acid, 1.5g green tea extract, 1.5g glutathione, 8g rose essential oil, 2g microcrystalline cellulose, and 70g water.

[0074] Green tea extract is prepared by the following steps: 8g of freshly picked green tea leaves are crushed, first extracted with 40g of 55% ethanol aqueous solution by mass for 3h, then extracted with 30g of 75% ethanol aqueous solution by mass for 90min, the extracts are combined, and the ethanol is recovered by vacuum distillation and concentrated to a water content of 25%. Then, 40g of chloroform is added, stirred at a speed of 150r / min for 90min, allowed to stand and separate, and the upper layer solution is freeze-dried.

[0075] The method for preparing the above-mentioned condom bubble lubricant containing hyaluronic acid comprises the following steps:

[0076] S1. Sodium alginate, calcium EDTA, and hyaluronic acid were added to 25 g of water, stirred and dissolved at 60° C. Nano-silica was added thereto and stirred for 90 min at a stirring speed of 100 rpm to obtain an aqueous phase.

[0077] S2. Add Span 60 to palm oil and stir evenly to obtain an oil phase;

[0078] S3. The aqueous phase and the oil phase are injected into the microchannel of the microfluidic device respectively by a syringe through a constant flow pump, the flow rate of the aqueous phase is 260 μL / h, and the flow rate of the oil phase is 700 μL / h, wherein the oil phase shears the aqueous phase into an oil-in-water emulsion; citric acid is added thereto under stirring, ultrasonic treatment is performed for 90 seconds, the ultrasonic frequency is 7.5 kHz, and the oil phase is removed by standing. Green tea extract, glutathione, rose essential oil, microcrystalline cellulose, and 45 g of water are added to the product, and the mixture is stirred at a temperature of 45°C for 20 minutes. The pH value of the system is adjusted to 5.5-6.5.

[0079] The lubricants obtained in Example 5 and Comparative Examples 1-2 were visually observed for transparency, floccules, stratification, and crystallization. It was found that all lubricants in each group were transparent and free of floccules, stratification, and crystallization.

[0080] The viscosity of the lubricants obtained in Example 5 and Comparative Examples 1-2 was measured at room temperature (25°C) using a digital viscometer (rotor No. 2, 12 rpm). The lubricity of the lubricants obtained in Example 5 and Comparative Examples 1-2 was also measured using a multifunctional friction and wear tester.

[0081] like Figure 1 As shown, the viscosity and friction coefficient of the lubricant obtained in Example 5 are the lowest, which are better than those of Comparative Examples 1-2 (P < 0.05).

[0082] 5g of each lubricant from Example 5 and Comparative Examples 1-2 were placed in a weighing bottle, uncovered, and placed in a constant temperature and humidity chamber at 40°C and 30% RH for 24 hours. The bottles were then weighed and the mass difference calculated. The smaller the mass difference, the better the moisturizing properties.

[0083] Quality difference = (G1-G2) ÷ (G1-G) × 100

[0084] Wherein, G1 is the initial weight (weighing bottle + lubricant), G2 is the weight after 24 h (weighing bottle + lubricant), and G is the weight of the weighing bottle.

[0085] In order to examine whether the use of water-soluble personal lubricants in condoms affects their mechanical properties, condom bursting volume and pressure tests were conducted.

[0086] Reference was made to the guidance for accelerated aging studies in GB / T 7544-2019, "Technical Requirements and Test Methods for Natural Rubber Latex Male Condoms," to observe and replicate the failure modes predicted by high-barrier condom stability studies at 30°C. Each group was aged in an aging chamber at 70±2°C, with 300 samples sampled for 7 days. The burst pressure was measured before and after aging, and the burst pressure retention was calculated.

[0087] Retention rate = bursting pressure after aging ÷ bursting pressure before aging × 100%

[0088] like Figure 2 As shown, the lubricant obtained in Example 5 has the smallest quality difference, indicating that it has the best moisturizing performance. Moreover, the lubricant obtained in Example 5 is used for condoms and still maintains a high burst pressure after aging, without affecting the mechanical properties of the condoms.

[0089] The antibacterial rates of the lubricants obtained in Example 5 and Comparative Examples 1-2 were measured according to Appendix C of GB 15979-2002 "Hygiene Standard for Disposable Sanitary Products".

[0090] Test strains: Escherichia coli 8099 and Staphylococcus aureus ATCC 6538, provided by the China Industrial Microbiology Culture Collection, fresh slant cultures of passages 4-8; Candida albicans ATCC 10231, provided by the China Industrial Microbiology Culture Collection, fresh slant cultures of passages 5-6. Test temperature: 19-21°C, exposure time: 5 minutes.

[0091] like Figure 3 As shown, the lubricant obtained in Example 5 has the highest antibacterial rate against the three test strains, which is better than that of Comparative Examples 1-2 (P < 0.05).

[0092] With reference to the vaginal irritation test method specified in the Technical Specifications for Disinfection (2002 edition), healthy, young adult, non-estrous female New Zealand rabbits were selected. Before the test, the animals' vaginal openings were inspected for discharge, congestion, edema, and other injuries. The rabbits were divided into Example 5, Comparative Example 1, Comparative Example 2, and a control group, with 3 rabbits in each group.

[0093] The animal was positioned supine, with the vaginal opening exposed. A catheter moistened with saline was gently inserted into the vagina (4-5 cm). 2 mL of the test solution was slowly injected using a syringe. The catheter was then withdrawn to complete the exposure. A control group of animals was treated similarly with saline. Each treatment was repeated 24 hours apart for 5 consecutive days.

[0094] 24 hours after the last contact, the animals were killed by air embolism, the vagina was completely removed and then longitudinally incised, and the mucosa was observed with the naked eye for edema, congestion, etc., and then fixed in 10% formaldehyde solution for 48 hours. Tissues from the two ends and three middle parts of the vagina were selected for preparation and HE staining for histopathological examination.

[0095] The histopathological examination results were scored. The irritation response scores of the three sites of the three animals in each group were summed and then divided by the total number of observations (number of animals × 3) to obtain the average score of the vaginal mucosal irritation response of the test group. The irritation index was calculated by subtracting the average score of the control group from the average score of Groups 9 and 10, and the irritation intensity was then graded.

[0096] The vaginal mucosal irritation response scores are shown in Table 3.

[0097] Table 1 Summary of vaginal mucosal irritation response scores

[0098]

[0099]

[0100] Note:

[0101] 1) Average score = sum of the stimulation response scores of 3 sites in 3 animals / total number of observations (number of animals × 3);

[0102] 2) Irritation index = average score of the poisoned group - average score of the control group.

[0103] As shown in Table 1, the lubricant obtained in Example 5 has an irritation index of only 0.33 on the vaginal mucosa of rabbits, and the vaginal mucosal irritation reaction intensity is non-irritating to the vaginal mucosa. The test results meet the requirements of the "Technical Specifications for Disinfection" (2002 edition).

[0104] Skin sensitization testing was conducted according to ISO 10993-10:2010, using the guinea pig maximum limit method and 0.9% sodium chloride injection extraction. Grade 0 represents no sensitization, and grades 1-3 correspond to mild to severe sensitization, respectively. The lubricants obtained in Example 5 and Comparative Examples 1-2 did not cause any sensitization.

[0105] The applicant believes that this is because the present invention uses hyaluronic acid in combination with sodium alginate and calcium EDTA, which are dissolved in water to form an aqueous phase. By controlling the ratio and flow rate of the aqueous phase to the oil phase, a water-in-oil emulsion is formed through shearing. The aqueous phase droplets have a low density and therefore float on the upper layer of the oil phase. The addition of citric acid to the emulsion system diffuses into the aqueous phase, causing the calcium EDTA to become less stable, thereby becoming free and combining with sodium alginate to form gel-like droplets. Further removal of the oil phase results in hydrophilic droplet particles that not only have excellent lubrication but also excellent moisturizing and soothing effects. They further synergize with green tea extract and glutathione, exhibiting good affinity and extremely high mutual dispersion uniformity, significantly improving vaginal dryness, while also providing excellent cleansing and lubricating effects, and exhibiting good antibacterial and antipruritic effects. The present invention uses dialdehyde cellulose in combination with the phenolic hydroxyl groups on the green tea extract, effectively extending the bactericidal and antibacterial effects and, in combination with glutathione, effectively neutralizing oxidation, protecting vaginal cells from oxidative damage. The present invention can effectively avoid the occurrence of problems such as allergies, and at the same time, there is no sticky feeling after use, the lubrication time is long, and good comfort and natural feeling can be effectively provided.

[0106] The above description is only a preferred specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any technician familiar with the technical field, within the technical scope disclosed by the present invention, who makes equivalent replacements or changes based on the technical solution and inventive concept of the present invention, should be covered by the scope of protection of the present invention.

Claims

1. A condom bubble lubricant containing hyaluronic acid, characterized in that: The raw materials include, by mass, 5-10 parts of hyaluronic acid, 1-3 parts of sodium alginate, 0.01-0.1 parts of calcium edetate, 1-2 parts of nano-silicon dioxide, 1-2 parts of surfactant, 60-120 parts of vegetable oil, 1-2 parts of citric acid, 1-2 parts of green tea extract, 1-2 parts of glutathione, 5-10 parts of plant essential oil, 1-3 parts of dialdehyde cellulose, and 50-90 parts of water.

2. The condom bubble lubricant containing hyaluronic acid according to claim 1, characterized in that: The surfactant is at least one of lauryl alcohol polyoxyethylene ether, stearyl alcohol polyoxyethylene ether, hexadecyl polyoxyethylene ether, cetearyl alcohol polyoxyethylene ether, sorbitan fatty acid ester, and polyoxyethylene sorbitan fatty acid ester.

3. The condom bubble lubricant containing hyaluronic acid according to claim 1, characterized in that: The vegetable oil is at least one of peanut oil, rapeseed oil, corn oil, camellia oil, walnut oil, olive oil, palm oil, grapeseed oil, and sunflower oil.

4. The condom bubble lubricant containing hyaluronic acid according to claim 1, characterized in that: Green tea extract is prepared by the following steps: freshly picked green tea leaves are crushed, first extracted with a 50-60% by mass ethanol aqueous solution under reflux for 2-4 hours, then extracted with a 70-80% by mass ethanol aqueous solution under reflux for 1-2 hours, the extracts are combined, and the ethanol is recovered by vacuum distillation and concentrated. Chloroform is then added and stirred for 1-2 hours. The mixture is allowed to stand to separate layers, and the upper layer is freeze-dried.

5. The condom bubble lubricant containing hyaluronic acid according to claim 4, characterized in that: The mass ratio of the freshly picked green tea leaves to the ethanol aqueous solution with a mass fraction of 50-60%, the ethanol aqueous solution with a mass fraction of 70-80%, and the chloroform is 5-10:30-50:20-40:30-50.

6. The condom bubble lubricant containing hyaluronic acid according to claim 1, characterized in that: The plant essential oils are rose essential oil, ylang-ylang essential oil, sandalwood essential oil or / and maca essential oil.

7. A method for preparing a condom bubble lubricant containing hyaluronic acid according to any one of claims 1 to 6, characterized in that: The steps include: S1. Add sodium alginate, calcium EDTA, and hyaluronic acid to water, stir and dissolve at 55-65°C, add nano-silica and continue stirring for 1-2 hours to obtain an aqueous phase; S2. Adding a surfactant to the vegetable oil and stirring evenly to obtain an oil phase; S3. Prepare a water-in-oil emulsion from the aqueous phase and the oil phase by microfluidic droplet technology, then add citric acid thereto under stirring, ultrasonically treat for 1-2 minutes, let stand to remove the oil phase, add green tea extract, glutathione, plant essential oil, dialdehyde cellulose, and water to the product, stir at 40-50°C for 10-30 minutes, and adjust the pH value of the system to 5.5-6.

5.

8. The method for preparing a condom bubble lubricant containing hyaluronic acid according to claim 7, characterized in that: In S3, in the process of preparing the water-in-oil emulsion using microfluidic droplet technology, the water phase flow rate is 200-300 μL / h, and the oil phase flow rate is 600-800 μL / h.

9. The method for preparing a condom bubble lubricant containing hyaluronic acid according to claim 7, characterized in that: In S3, the ultrasound frequency is 5-12 kHz.

10. The method for preparing a condom bubble lubricant containing hyaluronic acid according to claim 7, characterized in that: The mass ratio of water used in S1 to water used in S3 is 20-30:30-60.